ℒ2 Gain Performance for a Class of Lipschitz Uncertain Nonlinear Systems via Variable Gain Robust Output Feedback Controllers - Hidetoshi Oya; Kojiro Hagino (Journal of Control Science and Engineering)
We consider a design problem of a variable gain robust output feedback controller with guaranteed ℒ2 gain performance for a class of Lipschitz uncertain nonlinear systems. The proposed variable gain robust output feedback controller achieves not only robust stability but also a specified ℒ2 gain performance. In this paper, we show that sufficient conditions for the existence of the proposed variable gain robust output feedback controller with guaranteed ℒ2 gain performance are given in terms of linear matrix inequalities (LMIs). Finally, a simple numerical example is included.